2011
DOI: 10.5194/nhess-11-797-2011
|View full text |Cite
|
Sign up to set email alerts
|

The legal status of Uncertainty

Abstract: Abstract.An exponential improvement of numerical weather prediction (NWP) models was observed during the last decade (Lynch, 2008). Civil Protection (CP) systems exploited Meteo services in order to redeploy their actions towards the prediction and prevention of events rather than towards an exclusively response-oriented mechanism 1 .Nevertheless, experience tells us that NWP models, even if assisted by real time observations, are far from being deterministic. Complications frequently emerge in medium to long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Control rooms can be found in nuclear power plants [30,11,31], mineral processing plants [28,29], oil refineries [48], emergency warning systems [36,23,3,49]. Although these existing works investigate the physical design of a room and its technological tools, only few of them are focused on analyzing organizational theory and issues [9,60,50].…”
Section: Control Roomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control rooms can be found in nuclear power plants [30,11,31], mineral processing plants [28,29], oil refineries [48], emergency warning systems [36,23,3,49]. Although these existing works investigate the physical design of a room and its technological tools, only few of them are focused on analyzing organizational theory and issues [9,60,50].…”
Section: Control Roomsmentioning
confidence: 99%
“…However, although these works have resulted in a better understanding of the procedural, cultural, and social aspects of control rooms in different scenarios, the challenge now is to recognize how those factors can influence decision-making in control rooms for disaster risk monitoring. This is particularly important once activities carried out by operators are often affected not only by the cognitive skills of each operator [3,14,29] but also by communication and collaboration between them [32,14,3]. As stated by Reed [45], decisionmaking preferences in organizations are often inconsistent, unstable, and externally driven; the linkages between decisions and actions are loosely-coupled and interactive rather than linear.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2006 and 2009, the percentage of false positive meteohydrogeological alerts issued in Italy rose from 37 to 65 % (Altamura et al, 2011).…”
Section: The Legal Implications Of Risk and Crisis Communicationmentioning
confidence: 99%
“…Several authors argue that the key reasons are not to be found in a rapid increase in meteorological events, but rather in the increase of legal cases involving the authorities in charge of issuing the warning (DPCM and CIMA, 2013;Altamura et al, 2011). In order not to face legal charges in case of a missed alarm, emergency managers adopted selfprotective behaviours by issuing a larger number of false positive alerts.…”
Section: The Legal Implications Of Risk and Crisis Communicationmentioning
confidence: 99%
See 1 more Smart Citation